ASSESSMENT OF THE INFLUENCE OF MARKETING RESEARCH ON THE DEVELOPMENT OF PRODUCT SALES CHANNELS (BY THE EXAMPLE OF SAMARKAND-APPAREL LLC) (Marketing Journal, 2025)
This article examines the analysis of general production indicators, increasing production volumes, product sales, distribution channels, complex industrial relations, satisfaction social needs for material and intangible goods, efficiency of production organization, reflection and consumption of goods and services.
Keywords: Enterprise; production; sales; product; competition; efficiency; need; market